A bibliometrics analysis of literature on information seeking behaviour in health sciences - Harande, Yahya Ibrahim (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2012)
The main purpose of the study was to identify and analyze published articles on information seeking behavior in the literature of health sciences bibliometrically. The study spans the period from 1967-2009. Twelve thousand (12,000) published papers on information seeking behavior in health sciences were identified and recognized as the database for the study. Out of this number; three thousand seven hundred (3,700) journal papers were analyzed for this study. This number constitutes thirty percent (30%) of the total number of the papers identified. The MEDLINE and SCOPUS on-line databases were considered the source for the data for the research .The data analyzed for this study were selected proportionately using the stratified sampling techniques. In order to have representation from the wide period covered in the research , Six year period was used in grouping data from 1967-2009 and this gives seven groups. The last group exceeded with one year. The study found that, the literature of health information seeking behaviour was dominated by multiple authorship papers. The degree of collaboration in the literature has further indicated that, throughout the period of the study, collaborative works took the centre stage. Subramanyam's method of determining the extent of author collaboration was used to arrive at this finding. The result of comparison between the productive and collaborative authors has shown positive correlation and relationship between the two entities. Spearman's p = 0.95 was found to be the result of the exercise. Also ten subjects were found to be dominant in the literature of health information seeking behavior. Among the Ten are Nursing, Health care, Medicine, STDs/AIDS, Women's health and Disease prevention. Among these subjects, Medicine was found to be most pronounced and active in this literature. Also ten most productive aspect of medicine subjects were recorded as follows, General medicine, Tropical medicine, Community medicine, Military medicine, Travel medicine, Clinical medicine, Emergency medicine, Psychosomatic medicine, Genetic medicine and Sports medicine. The literature of health information seeking behaviour was categorized under four categories by subject headings. The categories are Multi-disciplinarity journals, Broad scope journals, Single subject journals and Disease and problems journals. On the categorization of journals that participated in the growth of collaborative activities in the health information seeking behaviour, single subject journals outnumbered the rest of the journals with 38.34%. The literature of health information seeking behavior was found to be scattered in all the subjects under health sciences .The law of scattering was applied to this set of data and was found to be in conformity with Bradford's law of scattering. Thirteen journals were found to constitute the core of the literature. They are as follows: Social science and medicine, Nurse education today, Bulletin of medical library association, Journal of advanced nursing, Journal of medical library association, Journal of nursing education, International journal of psychoanalysis, BMC public health, Nurse education, Health communication, STDs, Journal of health communication and Patient education counseling. On the language of dispersion of the literature, English language was found to be the dominant language of dispersion of the literature. It recorded (97%) as against the other twenty three languages. The findings of the research would assist the acquisition and selection committee in their activities of selecting appropriate materials for their organizations. Authorities charged with the development and growth of health literature could also use the findings for budgetary allocations and related matters. Medical libraries may benefit from the findings.